2005
DOI: 10.1037/0022-006x.73.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Infidelity and Behavioral Couple Therapy: Optimism in the Face of Betrayal.

Abstract: Infidelity is a common issue with which distressed couples and their therapists grapple. However, there are no data on the efficacy of commonly used therapies to treat couples in which there has been an affair. In the present exploratory study, the authors examined the therapy outcomes of a sample of infidelity couples (n=19) who had participated in a randomized clinical trial of marital therapy (N=134). Results show that infidelity couples began treatment more distressed than noninfidelity couples; however, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
2
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 17 publications
(27 reference statements)
2
85
2
3
Order By: Relevance
“…As part of this efficacy research, there were several additional findings: couples with lowlevel violence could benefit from treatment without a danger for violence escalating [12]; couples experiencing infidelity could benefit from treatment in the short term and, although these couples are at greater risk for separation over the long-term, those who stay together benefit as much as non-infidelity couples [13][14]; for couples with children, treatment showed benefits for parenting [15]. Prediction studies demonstrated that, out of a number of possible variables, higher relationship commitment and longer length of marriage were independently predictive of long-term positive outcome [16][17].…”
Section: Evidence In Support Of Ibctmentioning
confidence: 99%
“…As part of this efficacy research, there were several additional findings: couples with lowlevel violence could benefit from treatment without a danger for violence escalating [12]; couples experiencing infidelity could benefit from treatment in the short term and, although these couples are at greater risk for separation over the long-term, those who stay together benefit as much as non-infidelity couples [13][14]; for couples with children, treatment showed benefits for parenting [15]. Prediction studies demonstrated that, out of a number of possible variables, higher relationship commitment and longer length of marriage were independently predictive of long-term positive outcome [16][17].…”
Section: Evidence In Support Of Ibctmentioning
confidence: 99%
“…Independence, whether emotional or economical, is also an influencing factor in the decision for engagement (Drigotas & Barta, 2012). Aside from women entering the world of work (Atkins, Eldridge, Baucom, & Christensen, 2005;Drigotas & Barta, 2012), Weeks, in an interview conducted by Smith (2011), argued that the introduction of mobile and digital technology created more opportunities for EMR. Also, the mass media with its bombardment of subliminal to intentional messages about liberal sexuality, misrepresented and misinterpreted gender role changes, and equality and romanticized affairs is preparing a society that is more conducive to extra-dyadic affairs (Leyson, 2004(Leyson, -2006.…”
Section: Triggering Factorsmentioning
confidence: 99%
“…This problem is also particularly difficult to address in treatment because it frequently puts partners in a situation where they question their desire to continue their relationship [48,49]. This being said, many studies have concluded in the effectiveness of CBCT in the treatment of extradyadic affairs in terms of decreased psychological symptoms of depression and relationship distress [40,50,51]. Since CBCT commonly addresses infidelity as a form of interpersonal trauma experienced within the intimate relationship [52], interventions for this problem generally aim at dealing with the crisis following disclosure of the extradyadic affair and at the exploration of factors that might have contributed to the affair.…”
Section: Infidelity/extradyadic Affairsmentioning
confidence: 99%